Brenda Cranney. Local Environment and Lived Experience: The Mountain Women of Himachal Pradesh. New Delhi: Sage Publications, 2001. Hardbound. 287 pages. Indian Rs 495.00. (The Pakistan Development Review, 2001)
Rural communities in the less developed countries depend for their livelihood on a subsistence economy based on agriculture and animal husbandry. So is the case of rural communities in India. The state of Himachal Pradesh is an example where forests are the main source of food and income. Inappropriate or badly managed development programmes in these areas have resulted in the depletion of natural resources, causing environmental degradation. This naturally affects the lives of the local population, especially the poor women of the area, as forests provide the main source of output vital to their household economy. Local Environment and Lived Experience is the microanalysis of women in the two villages, Ichasser and Dev Nagar, in the state of Himachal Pradesh. It provides a critical overview of development programmes and how these programmes have changed the daily pattern of their lives. The change is explained in the own voices of local women—describing their intervention, coping strategies, and resistance. The author has explored different features of village life, household economies as well as women’s agency affected by the implementation and abandonment of development programmes.